ANALYSIS OF DISCRETE DATA USING LINEAR REGRESSION - J. Flowers, Robert (Ecosistemas y Recursos Agropecuarios, 2014)
Maximum likelihood estimates are obtained for a linear regressio model where the dependent variable is a linear transformation of mutinomially distributed random variables.